IDENTIFICATION OF DISCOVERY LEARNING METHODS TO INCREASE STUDENT LEARNING MOTIVATION - Mansyur, Haris; Oktavia, Sri Wina; Andriyanto, Andriyanto; Susbiyanto, Susbiyanto (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
The Discovery Learning method is designed to enhance students' learning experiences by encouraging them to actively explore, investigate, and discover knowledge on their own, leading to better retention and understanding. Edutainment, on the other hand, is an approach that integrates educational content with entertainment, making the learning process enjoyable and engaging. This study employs a literature review methodology to examine the potential of combining these two approaches to boost student motivation, specifically by utilizing the Zenius website. Zenius is recognized for its user-friendly interface and engaging content, making it an ideal platform for implementing Discovery Learning and Edutainment. By leveraging Zenius, the study aims to explore how these methods can create a more motivating learning environment for students, particularly in challenging subjects like Business and Energy. The findings are expected to provide insights into effective strategies for integrating technology and innovative learning methods in education.